Spirit of Legality: Hegel’s Critique of Law and Turn to Ontology in the Frankfurt Fragments - Dumbliauskas, Povilas (Religija ir kultūra, 2018)
This paper is an attempt to investigate the relation between George Wilhelm Friedrich Hegel’s critique of law in his early Frankfurt fragments, most notably in the treatise Spirit of Christianity and Its Fate and his turn towards an ontological conception of the unity of life and love as its modification. It will be argued that Hegel’s ontological turn can only be understood in light of his rejection of law as the form of absolute opposition. The form of law, moreover, will be treated as the thread to understand the initial movement of Hegel’s profound rejection of Kantian morality. Nevertheless, in following the Christian concept of pleroma that promises to fulfil law and proposing to think unification ontologically, Hegel discovers that law cannot be simply rejected, but pertains or arises out of the very unity that was said to surmount it. If Hegel begins from an opposition of law and being, these fragments reveal the extent to which he will have to think their relationship dialectically, as a contradiction pertaining to the Absolute.
Keywords: legality; pleroma; love; unity; negativity